2019
DOI: 10.1111/gcbb.12584
|View full text |Cite
|
Sign up to set email alerts
|

Miscanthus for biogas production: Influence of harvest date and ensiling on digestibility and methane hectare yield

Abstract: The 8,000 biogas plants currently in operation in Germany are mainly fed with biomass from annual crops. However, feedstock from perennial crops such as miscanthus is expected to be more environmentally benign. If miscanthus is to be used in greater amounts as a substrate for anaerobic digestion, storage will become a relevant topic, as a continuous supply of biomass throughout the year is necessary. The objective of this study was to identify the miscanthus harvest time that best balances the simultaneous ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 29 publications
1
35
1
Order By: Relevance
“…In addition, Mangold et al. (2018b) showed that the ensiling of miscanthus biomass reduces the necessary intensity of pretreatment. Besides the economic performance, this would also improve the environmental performance of miscanthus‐based biogas production.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Mangold et al. (2018b) showed that the ensiling of miscanthus biomass reduces the necessary intensity of pretreatment. Besides the economic performance, this would also improve the environmental performance of miscanthus‐based biogas production.…”
Section: Discussionmentioning
confidence: 99%
“…So far, ensiling is the best‐known preservation technique for biomass. (Mangold et al, ) demonstrated the ensiling ability of miscanthus biomass and showed positive effects of ensiled miscanthus on digestion‐velocity compared to nonensiled miscanthus. Mass losses of up to 7.6% of fresh matter for the Miscanthus sinensis genotype Sin55 were compensated by a higher substrate‐specific methane yield (up to 353 ml CH 4 (g oDM) –1 ), which resulted in a methane hectare yield of 4757 m 3 CH 4 ha –1 for ensiled miscanthus (Mangold et al, ).…”
Section: Substratesmentioning
confidence: 99%
“…(Mangold et al, ) demonstrated the ensiling ability of miscanthus biomass and showed positive effects of ensiled miscanthus on digestion‐velocity compared to nonensiled miscanthus. Mass losses of up to 7.6% of fresh matter for the Miscanthus sinensis genotype Sin55 were compensated by a higher substrate‐specific methane yield (up to 353 ml CH 4 (g oDM) –1 ), which resulted in a methane hectare yield of 4757 m 3 CH 4 ha –1 for ensiled miscanthus (Mangold et al, ). To enable a large‐scale use of perennial crops such as miscanthus, implementation barriers must first be removed for farmers who are afraid of a 20‐year fixation of the land to one crop with above‐average initial investments.…”
Section: Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge is dealing with the ensiling and the lower specific methane yield of the lignocellulosic miscanthus biomass. Mangold, Lewandowski, Hartung and Kiesel () show that ensiling miscanthus biomass is possible and that the specific methane yield can be improved by green harvesting in October. Another advantage of miscanthus over maize is its ability to grow on land with biophysical constraints to food crop production.…”
Section: Biogas Sectionmentioning
confidence: 99%